2001
DOI: 10.1590/s1516-31802001000400003
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in blood donors

Abstract: CONTEXT: Blood donation results in a substantial loss of iron (200 to 250 mg) at each bleeding procedure (425 to 475 ml) and subsequent mobilization of iron from body stores. Recent reports have shown that body iron reserves generally are small and iron depletion is more frequent in blood donors than in non-donors. OBJECTIVE: The aim of this study was to evaluate the frequency of iron deficiency in blood donors and to establish the frequency of iron deficiency in blood donors according to sex, whether they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
1
13

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 11 publications
9
54
1
13
Order By: Relevance
“…Cancado et al [8] found that the frequency of iron deficiency was higher among male donors with three or more donations per year and among the women with two or more donations per year. The results of all these studies were similar to our findings and showed the importance of measuring iron stores as an indicator for being selected for blood donation.…”
Section: Resultsmentioning
confidence: 99%
“…Cancado et al [8] found that the frequency of iron deficiency was higher among male donors with three or more donations per year and among the women with two or more donations per year. The results of all these studies were similar to our findings and showed the importance of measuring iron stores as an indicator for being selected for blood donation.…”
Section: Resultsmentioning
confidence: 99%
“…5 Indeed, blood donation can result in reduction of body iron stores. 7,17 Considering that iron deficiency has been defined as SF concentrations < 12 ng/ml, 16 no one in this study had iron deficiency according to SF levels. Although iron intake in the current study was lower than the Dietary Reference Intake (DRI) (around 7 mg/day rather than the recommended 8 mg/day), the subjects' diet was composed of low to moderate amounts of iron absorption inhibitory factors, high quantities of iron absorption enhancers and foods with highly bioavailable iron.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is further important to mention that to replenish the iron store even in mild degree of anaemia needs the dietary care and specific treatment for at least three months, even if the Hb level is being corrected much earlier. 1,3,5,[14][15][16][17][18][19][20] The lower the SF level, higher will be the possibility to suffer from anaemia i.e., potentially anaemic. Prevention of iron deficiency is essential as it is well known that anaemia causes non-specific symptoms like tiredness, weakness, headache, breathlessness, irritability, including the decreased work capacity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Blood donation results in a substantial (200-250mg) loss of iron at each bleeding procedure (425-475ml) and therefore, the frequency of blood donation is so adjusted as to prevent anaemia in most donors. 3 However, the effect of blood donation on the status of total body iron content is often neglected, despite the fact that body iron reserve is small and therefore, iron depletion is better to be considered at least in blood donors and especially in repeat donors. 4,5 In the majority of blood banks, haemoglobin and/or haematocrit measurements are used as routine screening tests for allowing a person to donate blood.…”
Section: Introductionmentioning
confidence: 99%